Economic Analyses of Small holder Rice Farmers in Kebbi State, Nigeria - Danmaigoro, Aliyu; Ahmad , Asmau; Yahaya Sanda, Hassan; Audu, Sanusi (MultiTech Publisher, 2023)
This study examined the economic analysis of rice production in Kebbi State, Nigeria. The specific objectives were to identify the socio-economic characteristics of the respondents, estimate the cost and returns, and evaluate the efficiency of resource use. Primary data were used in the study. They were obtained through a questionnaire A total of 160 rice farmers engaged in rice production were investigated. The collated data were analyzed using descriptive statistics, budgetary analysis, and resource use efficiency models. Results from the analyzes revealed that most rice farmers were above productive age, experienced, and could read and write. Empirical results also revealed that rice production is viable with approximately 40% return on investment for every N1 invested in the rice farming enterprise. Resource use efficiency in the study area showed underutilization of seed, farm size, fertilizer, and agrochemicals. It is recommended that the farmers in the study area should be provided with farm input and improved technologies, which could enable them to become more efficient in rice production and further guarantee sustainable growth and food security.